The investigation of the skin biophysical measurements focusing on daily activities, skin care habits, and gender differences - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan Jawad (John Wiley and Sons Ltd., 2016)
Background Skin, as a protective barrier to exogenous substances, can be modulated by various internal and external factors that can affect its functional state. In order to prevent the early symptoms and signs of diseases of the skin, frequent skin health assessment should be performed. The aims of the study were to evaluate four skin properties of transepidermal water loss (TEWL), hydration, elasticity, and pigmentation using a non-invasive skin assessment tool, DermaLab Combo®, and also to determine possible factors that may influence skin condition.